1998
DOI: 10.1164/ajrccm.158.2.9711107
|View full text |Cite
|
Sign up to set email alerts
|

Combined Surfactant Therapy and Inhaled Nitric Oxide in Rabbits with Oleic Acid-induced Acute Respiratory Distress Syndrome

Abstract: Intratracheal administration of surfactant and inhaled nitric oxide (INO) have had variable effects in clinical trials on patients with acute respiratory distress syndrome (ARDS). We hypothesized that combined treatment with exogenous surfactant and INO may have effects in experimental ARDS. After intravenous infusion of oleic acid in adult rabbits and 4-6 h of ventilation, there was more than a 40% reduction in both dynamic compliance (Cdyn) of the respiratory system and functional residual capacity (FRC), a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
1
2

Year Published

2000
2000
2011
2011

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(28 citation statements)
references
References 34 publications
2
23
1
2
Order By: Relevance
“…The present results are in contrast with some data previously reported, but in the experiments by Dahm et al [4] and Zhu et al [6], the absence of effects of NO inhalation on respiratory system resistance was evaluated in endotoxin- or oleic acid-induced lung injury, respectively, and Zhang et al [5]simply reported that NO inhalation did not adversely affect basal respiratory system resistance. In the experiments by Kips et al [11] and Maniscalco et al [12], no significant effect of L -NAME was detected on basal respiratory system resistance in healthy rats or humans, respectively, but the L -NAME dosages were much lower than the dosage presently used.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…The present results are in contrast with some data previously reported, but in the experiments by Dahm et al [4] and Zhu et al [6], the absence of effects of NO inhalation on respiratory system resistance was evaluated in endotoxin- or oleic acid-induced lung injury, respectively, and Zhang et al [5]simply reported that NO inhalation did not adversely affect basal respiratory system resistance. In the experiments by Kips et al [11] and Maniscalco et al [12], no significant effect of L -NAME was detected on basal respiratory system resistance in healthy rats or humans, respectively, but the L -NAME dosages were much lower than the dosage presently used.…”
Section: Discussioncontrasting
confidence: 99%
“…The same result has been also confirmed by data obtained by Zhu et al [6] on a rabbit experimental model of oleic acid-induced respiratory distress syndrome: no effect of isolated NO inhalation on the bronchoalveolar lavage fluid content of tensioactive desaturated phosphatidylcholine was detected. In contrast, Storme et al [17] reported increased hysteresis areas as an effect of NO inhalation, but their data were probably influenced by the confounding effects of long-lasting 100% oxygen inhalation.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…148,149 In contrast, animal models of indirect lung injury generally respond less well to surfactant administration. Injury from oleic acid infusion via the pulmonary artery shows almost no improvement with surfactant, 150 although many would argue that this is a lethal injury with substantial cellular disruption 151 that is unlikely to respond to any therapy. A porcine sepsis model that used intravenous lipopolysaccharide infusion showed some oxygenation improvement following surfactant administration, 152,153 but the response was less striking than in the surfactant-treated animals injured with intratracheal lipopolysaccharide above.…”
Section: Animal Studies Of Surfactantmentioning
confidence: 99%
“…Дополнитель ными факторами повреждения лёгочной ткани и сурфактантной системы являются волюмотравма, баротравма и токсическое действие высоких концен траций О 2 . В эксперименте был продемонстрирован синергизм действия иNO и экзогенного сурфактанта на артериальную оксигенацию [16]. Усиление дейст вия иNO объясняют, прежде всего, рекрутирующим и стабилизирующим действием экзогенного сурфак танта, приводящим к увеличению числа альвеол, до ступных для поступления лечебного газа [6].…”
Section: острое повреждение легких острый респираторный дистресс синunclassified